PENGARUH PENERAPAN DISIPLIN DI SEKOLAH TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA DAN KEWARGANEGERAAN (PPKn) SISWA KELAS X SMA NEGERI 4 BAGAN SINEMBAH - RISMA WATI SITORUS; Gimin '; Zahirman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study is based on a student with such SMA Negeri 4 Bagan Sinembah that affect their learning outcomes, a tendency to not be eliminated discipline in students in order to achieve maximum learning results, acts of indisipline arrive late, do not wear school uniform in accordance with School, and many more. In teaching and learning outcomes that satisfy the student are required to discipline, both within the school and outside of school and living environment. The problem in this research is how the effect of the application of school to the learning outcomes of Pancasila and Citizenship education class X SMA Negeri 4 Bagan Sinembah. The study aims to determine the effect of the application of school to the learning outcomes of Pancasila and Citizenship education class X SMA Negeri 4 Bagan Sinembah. This research was conducted in SMA Negeri 4 Bagan sinembah Disctrict Rokan Hilir with the population 128 people and sample 32 people. This File collection techniques were collected through observation, questionnaire, and documentation. Research result the effect of the application of school to the learning outcomes of Pancasila and Citizenship education class X SMA Negeri 4 Bagan Sinembah is significant or affected positively by Y =12,852 + 0,145X. In means constant value 12,852 of which means that if the application of discipline in school is assumed not to exist, then the result is worth unit students learn citizenship. The effect of the application of discipline in shool on learning outcomes can be seen from the regression coefficient which direction relations are positive signs that describe that positive relationship which means that if the application of discipline in schools increased by one unit then PPKn student learning outcomes obtained for 0,145 the unit.Keywords: Application, Discipline, Student Learning Outcomes2